Larger infarct size but equal protection by ischemic conditioning in septum and anterior free wall of pigs with LAD occlusion - Skyschally, Andreas (Physiol Rep, 2019)
The ischemic area at risk (AAR) is one major determinant of infarct size (IS). In patients, the largest AAR is seen with a proximal occlusion of the left anterior descending (LAD) coronary artery, which serves parts of the septum and of the anterior free wall. It is not clear, whether regional differences in the perfusion territories also impact on IS and the magnitude of cardioprotection by ischemic conditioning. We have retrospectively analyzed 132 experiments in pigs, which have a similar LAD perfusion territory as humans. The LAD was occluded for 60 min with subsequent 180 min reperfusion. Cardioprotection by either local ischemic pre‐ or postconditioning or remote ischemic pre‐ or perconditioning was induced in 93 pigs. The AAR was demarcated by blue dye staining, and IS was assessed by triphenyltetrazolium chloride (TTC) staining. Using digital planimetry, the AAR was separated into sections unequivocally located in the septum (AAR(S)) or the anterior free wall (AAR(AFW)). Relative IS was calculated for AAR(S) or AAR(AFW). AAR(AFW) was larger than AAR(S) (51 ± 9% vs. 34 ± 8% of total AAR; mean ± SD, P < 0.001). Regional myocardial blood flow (microspheres) was not different between septum and anterior free wall. IS without ischemic conditioning tended to be larger in AAR(S) than in AAR(AFW) (50 ± 17% vs. 44 ± 19%; % of AAR(AWF) or AAR(S), respectively; P = 0.075). Also, with robust IS reduction by ischemic conditioning, the difference in relative IS remained (AAR(S): 27 ± 16%; AAR(AFW): 21 ± 16%; P = 0.01). There is a somewhat greater susceptibility for infarction in septal than anterior free wall myocardium. However, ischemic conditioning still reduces IS in both septal and anterior free wall myocardium.